Foresight Study on Solar Photovoltaic (PV) Adaptation in Damansara Emas Residential Area - Rodzalan, Shazaitul Azreen; Hao Lun, Bee (Research in Management of Technology and Business, 2024)
Solar Photovoltaic (PV) is a way to generate renewable energy that is friendly to environment. Many incentives adoption in Malaysia is rather slow in residential area, Net Energy Metering system (NEM) and Feed-in Tariff (FiT) are incentives that are provided by Malaysian Government but the adaptation rate is still rather low and slow. Thus, this research intends to identify the key drivers of rooftop solar PV adaptation among residential in Malaysia or forecast the future trends within the residential area in Malaysia, specifically, Damansara Emas, Malaysia. The approach for this study consisted of foresight analysis on Solar PV adaptation impact-uncertainty analysis, and scenario analysis. This study used STEEPV analysis to examine the issues and drivers related to Solar PV. A total of 180 residents from Damansara Emas were involved in completing the survey. The result of the survey concluded that cost-effective of technology increase the rate of Solar PV adaptation, and secondly the incentives and government policy to resident, these were discovered from scenario building. This research will give benefits to resident in residential area with potential to adapting the technology and government motives to increase the renewable energy sources in country, there fore early precaution and can be taken by stakeholders and adopters.